Student teachers as tutors for children in an inner city school - Levine, Murray; Dunn, Freda; Brochinsky, Steve; Bradley, Jesse; Donlan, Kay (Child Psychiatry & Human Development, 1970)
A tutoring program for first grade inner city children, employing student teachers as tutors, was developed and evaluated. Tutoring had no discernible effects on performance on the Illinois Test of Psycholinguistic Ability. However, tutored children were placed in the highest reading group, and were rated by the regular classroom teacher as having completed the first grade reading series more often than controls. Tutors saw their children as becoming more responsive over time. Classroom teachers rated the tutored children as more competent in the classroom, more confident, and as viewing the classroom as more benevolent. In contrast to controls, student teachers maintained favorable attitudes toward teaching in the inner city, and they claimed to have benefited in practice teaching from their tutoring experience. However, relatively few actually took teaching positions in inner city schools after completing their training. © 1972 Behavioral Publications, Inc.
Keywords: dept.psy

The mental patient and civil rights: Some moral, legal, and ethical considerations. - Tolchin, Gerald; Steinfeld, George; Suchotliff, Leonard (Professional Psychology, 1970)
Distinguishes between legal, ethical, and egalitarian principles involving hospitalization of persons alleged to be mentally ill. With regard to the question of legality, the need for compilation and distribution of relevant information and for informing patients of their rights is discussed. The boundaries of psychologists' professional and personal ethics are viewed as helping patients obtain services which they are personally unable to provide and insuring that the welfare of the patient is placed before the interests of the institution. Egalitarian issues are discussed with regard to: (a) judging whether a mental patient is responsible for his words and actions; (b) the patient's right to accept, reject, or select treatment; and (c) hospitalization of general medical patients and their rights to be informed about their condition, to be notified of test results, and to know the name, quantity, and expected reaction to drugs they are given. It is suggested that psychologists have too long been silent on these issues and in the face of abuses, and that more discussion and stands on them are needed. (PsycINFO Database Record (c) 2006 APA, all rights reserved). © 1970 American Psychological Association.
Keywords: dept.psy; moral vs. legal vs. ethical considerations regarding hospitalization of mentally ill